2022
DOI: 10.3389/fnins.2022.858717
|View full text |Cite
|
Sign up to set email alerts
|

Regional Neural Activity Abnormalities and Whole-Brain Functional Connectivity Reorganization in Bulimia Nervosa: Evidence From Resting-State fMRI

Abstract: The management of eating behavior in bulimia nervosa (BN) patients is a complex process, and BN involves activity in multiple brain regions that integrate internal and external functional information. This functional information integration occurs in brain regions involved in reward, cognition, attention, memory, emotion, smell, taste, vision and so on. Although it has been reported that resting-state brain activity in BN patients is different from that of healthy controls, the neural mechanisms remain unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The finding that the SB and MB groups both showed lower lOFC-SPL connectivity strength than HC is in accordance with the results of a previous resting-state fMRI study ( Wang et al., 2022 ). As crucial hubs of the frontoparietal network, the lOFC and SPL have been implicated in initiating and modulating cognitive control abilities, such as the downregulation of inhibition and reappraisal of food carving ( Hollmann et al., 2012 ; Siep et al., 2012 ; Zanto & Gazzaley 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that the SB and MB groups both showed lower lOFC-SPL connectivity strength than HC is in accordance with the results of a previous resting-state fMRI study ( Wang et al., 2022 ). As crucial hubs of the frontoparietal network, the lOFC and SPL have been implicated in initiating and modulating cognitive control abilities, such as the downregulation of inhibition and reappraisal of food carving ( Hollmann et al., 2012 ; Siep et al., 2012 ; Zanto & Gazzaley 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Parallelly, we previously reported increased OFC volume in BN patients ( 38 ). Mounting researches have proved the involvement of the OFC in the neural mechanism of BN from the perspectives in brain activation pattern ( 39 ), structural network properties ( 11 ) and FC ( 8 ). OFC is involved in hedonic food processing and plays a central role in food value-directed eating behavior ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uher et al demonstrated diminished occipitotemporal responses in patients with BN when viewing their own abnormal body weight ( 7 ). Using the resting-state fMRI images (rs-fMRI), our previous study suggested aberrant regional activity in the left insula and bilateral inferior parietal lobule ( 8 ). Moreover, there is growing recognition that BN may result from abnormal information interaction between different functional centers or even across large-scale brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…Developing resting‐state functional magnetic resonance imaging (RS‐fMRI) technology has facilitated the discovery of neurobiological mechanisms of BN. Convergent evidence from RS‐fMRI has demonstrated that the bulimic behaviors in BN were associated not only with functional abnormalities in specific brain regions (Lavagnino et al, 2014; Li et al, 2022; Wang et al, 2022; Wang, Bi, et al, 2020) but also with disruptions in intrinsic functional brain networks (Amianto, D'Agata, et al, 2013; Li et al, 2018; Spalatro et al, 2019; Wang et al, 2017; Wang et al, 2019). In general, a healthy brain is an efficient network consisting of a series of highly functionally specialized and spatially separated modules (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%